Determinasi Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Jambi: Perspektif UMKM, Tenaga Kerja, Omset dan Pendidikan - Ratih Rosita; Yorina An’guna Bansa; Andri Devita; Asrini Asrini; Ika Dwimaya Roza; Dimas Kurniawan (Universitas Batanghari Jambi, 2026)
Sustainable regional economic development highly depends on the role of Micro, Small, and Medium Enterprises (MSMEs) and the quality of human resources. This study aims to analyze the relationship and influence of the number of MSMEs, MSME labor, MSME turnover, and education level on economic growth in 11 regencies/cities of Jambi Province during the 2019–2024 period. The study employs a quantitative approach using panel data (N = 66). Analysis was conducted through Pearson correlation and panel data regression with the Fixed Effect Model (FEM), selected based on the Chow and Hausman tests. Correlation results show that the number of MSMEs, MSME labor, and turnover have a positive relationship with economic growth, while education level has a negative and insignificant relationship. The FEM regression results reveal that all four variables simultaneously have a significant effect. Partially, the number of MSMEs and education level have a positive and significant effect, whereas MSME labor and turnover have a positive but insignificant effect. These findings indicate that regional economic growth is more determined by the expansion of MSMEs and the improvement of human resource quality rather than merely the quantity of labor or turnover. This study recommends a policy shift from quantity-driven growth toward productivity- and quality-driven growth.